Gallbladder polyps in familial adenomatous polyposis. (August 2017) - Balog, Martin; Kolbe, Ernst-Wolfgang; Lang, Ulrich; Winde, Guenther
Abstract : Introduction: Familiar adenomatous polyposis (FAP) is an inherited autosomal dominant disease characterized by the development of hundreds to thousands of colorectal adenomas in young adults. If left untreated, the patients develop colorectal cancer by age of 40. This disorder is caused by germline mutation of the adenomatous polyposis coli (APC) gene located on the chromosome 5q21. FAP can be associated with occur of various extracolonic malignancies, especially ampullary adenocarcinoma. As well it has been described an association between FAP, thyroid cancer and biliary system neoplasia. We present a rare case of multifocal gallbladder polyps in association with familial adenomatous polyposis. Case report: We present the case of a 39-year-old male patient with the FAP-Syndrome. He had undergone a total colectomy with ileoanal pouch reconstruction years ago. In the current history, he reported about chronic abdominal pain in the right upper abdomen with postprandial nausea. The clinical examination at the admission showed no palpable mass or tenderness in the abdomen. The laboratory tests were normal. Abdominal ultrasound showed four concrements and multiple small polyps. He underwent laparoscopic cholecystectomy. The postoperative course was uneventful. Results and conclusions: The mucosal inspection at the histopathological examination showed more than 80 green polypoid lesions. Microscopically were classified tubular adenomas with mostly low–grade but focally with high-grade epithelial dysplasia cells. Their epithelium was predominantly of the biliary type. No invasive malignant cells have been described. Immunohistochemical staining with ß-catenin showed strong positivity for cytoplasmic and nuclear expression. APC is closely connected to ß-catenin and a nuclear expression comes along with ß-catenin mutations. Nuclear staining has been described in adenocarcinomas and late adenomas with severe dysplasia. Take-home message: FAP is the most common adenomatous polyposis syndrome characterized by the development of numerous colorectal adenomatous polyps. It is associated with greater risk of developing upper gastrointestinal malignancy or extraintestinal cancer. Due to previous reports and our conclusions, a simultaneous prophylactic cholecystectomy should be performed by FAP patients, who undergo colectomy, to eliminate the risk of gallbladder neoplasia.